Integrasi Teknologi Dalam Kurikulum Pendidikan Untuk Meningkatkan Efektivitas Pembelajaran - Nola Agustin; Nur Faizah; Merika Setiawati; Hendri Budi Utama (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
Technology integration in the curriculum is one of the important strategies to improve the effectiveness of learning in the digital era. Rapid changes in the field of information technology have encouraged the world of education to adapt so that the teaching and learning process becomes more relevant, efficient, and interesting. The purpose of this study is the need for a curriculum for learning that is more adaptive and responsive to the challenges of the 21st century. A qualitative approach based on a literature review was used in this study. Information was collected from various printed and digital scientific publications. The main goal is to understand the value of integrating technology into the classroom and how to do it effectively. Digital learning applications and interactive media, according to research, can increase student engagement, promote material distribution, and improve teacher-student communication. However, the success of this integration is highly dependent on the readiness of teachers to adopt technology and the availability of adequate technological facilities. The conclusion of this study confirms that the integration of technology in the curriculum has a very positive impact, especially on the effectiveness of learning.